Dealing with the Menstruating Woman: A Comparative Study between Judaism and Islam - Basim Muhammed Kalash (Islamic Sciences Journal, 2025)
This study addresses the topic of dealing with women during menstruation in Judaism and Islam, using a comparative methodology between the foundational texts and legal rulings in each religion. The research relied on analyzing texts from the Torah and the Talmud in the Jewish context, and the Holy Quran and the Prophet's Sunnah in the Islamic context, referencing key commentaries and legal texts (Fiqh books). The study concluded that both religions view menstruation as a special state requiring legislative regulation, but with fundamental differences in application. In Judaism, the rulings focus on the concept of "Niddah" (ritual impurity), which necessitates strict physical and social separation, while in Islam, the rulings focus on ritual purity (Taharah) while maintaining the woman's dignity and the continuity of family life in most of its aspects. This study aims to provide an objective understanding of the legislative roots and the philosophies underlying these rulings.